Isothermal and Two-Temperature Zone Selenization of Mo Layers - L. Kaupmees; M. Altosaar; O. Volobujeva; T. Raadik; M. Grossberg; M. Danilson; E. Mellikov; P. Barvinschi (Advances in Materials Science and Engineering)
Glass/Mo, Mo foil, glass/Mo/In, and glass/Mo/Cu stacked layers were selenized in closed vacuum tubes by isothermal and/or two-temperature zone annealing in Se vapors. The selenization process was studied dependent on Se vapor pressure, temperature and time. Samples were selenized from 375 to 580°C for 30 and 60 minutes. The applied Se pressure was varied between 130 and 4.4⋅103 Pa. The increase of MoSe2 film thickness was found to depend on the origin of Mo. MoSe2 thickness dL on Mo-foil was much higher than on sputtered Mo layers, and it depended linearly on time and as a power function dL~PSe1/2 on Se vapor pressure. The residual oxygen content in the formed MoSe2 layers was much lower in the two-zone selenization process. If Mo was covered with Cu or In before selenization, these were found to diffuse into formed MoSe2 layer. All the MoSe2 layers showed p-type conductivity.